Melasolv™: a potential preventive and depigmenting agent for the senescence of melanocytes - Cho, Yeonju; Choi, Suh-Yeon; Choi, Hyunjung; Ham, Mira; Kim, Kyu-Han (Frontiers in Molecular Biosciences, 2024)
Senescent melanocytes are major contributors to age-related changes in the skin, highlighting the contribution of cellular aging to skin aging. Moreover, prolonged photodamage, such as that caused by UV exposure, can result in melanin accumulation and accelerated melanocyte senescence, thereby exacerbating aging. MelasolvTM is a substance that induces potent depigmentation effects and exhibits low toxicity. The present study aimed to investigate the potential effect of MelasolvTM on senescent melanocytes. We profiled the transcriptomics of MelasolvTM-treated melanocytes and identified the possible mechanism of action (MOA) and targets using connectivity mapping analysis. We identified differentially expressed genes in response to treatment with MelasolvTM using RNA-sequencing and validated the data using quantitative real-time PCR. Moreover, we performed an in vitro β-gal assay in senescent melanocytes for further validation. MelasolvTM reduced β-gal and melanin levels in senescent melanocytes. Moreover, the identified MOAs are associated with anti-aging and anti-senescence effects. Our findings clearly indicate that MelasolvTM not only exhibits anti-senescent properties but can also potentially alleviate melanin accumulation in senescent cells. These findings could have far-reaching implications in the treatment of age-related photodamaged skin conditions, such as senile lentigo and melasma.